Assessing the Circularity of Nutrient Flows Across Nested Scales for Four Food System Scenarios in the Okanagan Bioregion, BC Canada - Harder, Robin; Mullinix, Kent; Smukler, Sean (Frontiers in Sustainable Food Systems, 2021)
In light of continued nutrient pollution in water bodies and anticipated insecurities related to future nutrient supplies, there is an increasing awareness of the need to use nutrients in a more circular way. As part of a food system design study in the Okanagan bioregion, BC Canada we set out to evaluate different food system scenarios for the year 2050 in terms of nutrient circularity. In doing so, the objective was to evaluate the circularity of nutrient flows not only in the Okanagan, but also in relation to exogenous regions, insofar as nutrient flows relate to feed and food consumption and production in the Okanagan. This is important because feed and food trade means that nutrient inputs to crop production in the Okanagan may make their way into organic residuals outside the Okanagan, and vice versa. If not accounted for, this may lead to a distorted picture when analyzing nutrient circularity. To this effect, we applied an analytical framework and calculation model that explicitly tracks nutrients from crop production to organic residual generation. The results of the study suggest that assessing nutrient circularity across multiple scales was critical for two reasons. First, changes in overall nutrient flows in response to notably population increase and dietary change were found to be more pronounced outside the Okanagan. Second, our analysis clearly revealed the extent to which a higher level of nutrient circularity in the Okanagan comes at the expense of lowering the level of nutrient circularity elsewhere. This kind of analysis should therefore be useful to explore, ideally together with food system and organic residual management actors, how different food system and organic residual management scenarios perform in terms of nutrient circularity, in the geographical area being considered, but also how it impacts nutrient flows and circularity in the places with which feed and food are traded.